The War at Home : Perspectives on the Arkansas Experience during World War I - Christ, Mark K. (Book collections on Project MUSE., 2020)
"To commemorate the centennial of World War I, the Old State House Museum in Arkansas held a two seminars in 2017 and 2018. The subjects covered by some of the state's finest historians ranged from economic to medical to sociological. They included conflict surrounding intense industrialization, the development of a training facility for Doughboys sent to France, the murderous influenza of 1918, and the path from the Armistice to Pearl Harbor as seen through the lens of the state's newspapers. Equally important were the sociological considerations: women's mobilization for the war efforts as well as its link to suffrage, African American military service as well as black veteran experiences with the Elaine Race Massacre of 1919, and the role's war in addressing wounds and divisions still lingering from the Civil War era. These papers, collected in The War at Home, provide a thoughtful look into the many ways the Great War affected Arkansas and how that history plays out today. With contributions from Shawn Fisher, Elizabeth Griffin Hill, Carl Drexler, Cherisse Jones-Branch, Raymond Screws, Brian K. Mitchell, Thomas A. DeBlack, Jeannie Whayne, and Roger Pauly"--